Perilaku Pencarian Informasi Mahasiswa Program Sarjana Fakultas Ilmu Pengetahuan Budaya Universitas Indonesia Berbasis Sumber Literatur Elektronik dalam Era Digital - Wibowo, Muhamad Prabu; Inamullah, M. Hanif; Hariyadi, Utami Budi Rahayu (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2018)
This study examines the information seeking behavior of undergraduate students of the Faculty of Humanities Universitas Indonesia (FIB UI) related to the learning process in universities and evaluates the use of eresources subscribed by UI Library. This research adapts the model of information seeking behavior by Ellis, Cox and Hall (Behavioral Model of Information Seeking Strategies) which was later adapted by Wilson (a model of the Gross-Information Seeking Strategies) to analyze and provide a description of students’ information seeking behavior in supporting their learning process and research. Data were collected in this study through in-depth interviews and focus group discussions of 16 FIB UI students. The findings of this study indicate that students need information from e-resources for their academic purposes, such as doing their coursework. The findings also indicate that students are proficient in identifying the uniqueness of eresources subscribed by UI Library to meet their information needs. However, this study also found some obstacles that cause the less utilization of the e-resources, for example: lack of socialization and promotion, lack of integration with lecture activities, lack of encouragement from lecturers, and other individual issues. According to those findings, this study proposed several suggestions related to information search barriers, UI library should be more proactive in promoting its resources at student events; lecturers should be more active in directing students to use e-resources from UI Library, and the need for lectures that lead students in information searching strategy.